Excess risk of urinary tract cancers in patients receiving thiopurines for inflammatory bowel disease: a prospective observational cohort study. Issue 2 (9th November 2015) - Bourrier, A.; Carrat, F.; Colombel, J.‐F.; Bouvier, A.‐M.; Abitbol, V.; Marteau, P.; Cosnes, J.; Simon, T.; Peyrin‐Biroulet, L.; Beaugerie, L.; ,
Summary: Background: The risk of urinary tract cancers, including kidney and bladder cancers, was increased in transplant recipients receiving thiopurines. Aim: To assess the risk of urinary tract cancers in patients with inflammatory bowel disease (IBD) receiving thiopurines in the CESAME observational cohort. Methods: Between May 2004 and June 2005, 19 486 patients with IBD, 30.1% of whom were receiving thiopurines, were enrolled. Median follow‐up was 35 months (IQR: 29–40). Results: Ten and six patients developed respectively kidney and bladder cancer. The incidence rates of urinary tract cancer were 0.48/1000 patient‐years in patients receiving thiopurines (95% CI: 0.21–0.95), 0.10/1000 patient‐years in patients who discontinued thiopurines (95% CI: 0.00–0.56) and 0.30/1000 patient‐years in patients never treated with thiopurines (95% CI: 0.12–0.62) at entry. The standardised incidence ratio of urinary tract cancer was 3.40 (95% CI: 1.47–6.71, P = 0.006) in patients receiving thiopurines, 0.64 (95% CI: 0.01–3.56, P = 0.92) in patients previously exposed to thiopurines and 1.17 (95% CI: 0.47–12.42, P = 0.78) in patients never treated with thiopurines. The multivariate‐adjusted hazard ratio (HR) of urinary tract cancer between patients receiving thiopurines and those not receiving thiopurines was 2.82 (95% CI: 1.04–7.68, P = 0.04). Other significant risk factors were male gender (HR: 3.98, 95% CI: 1.12–14.10, P = 0.03) and increasing age (HR after 65 years (ref <50): 13.26, 95% CI: 3.52–50.03, P = 0.0001). Conclusion: Patients with IBD receiving thiopurines have an increased risk of urinary tract cancers. Clinically relevant excess risk is observed in older men.